Value of PET-CT Staging in Lymphoma Patients at Baseline over Clinical Staging (Bangladesh Journal of Nuclear Medicine, 2019)
Objectives:Lymphoma is the cancer of lymphatic system.Treatment strategy of lymphoma depends upon the staging of disease.Accurate staging can guide the required regimen and can minimize the therapeutic toxic effect and reduces the morbidity and mortality associated with over treatment. The purpose of this study was to observe the upstaging or down staging of lymphoma patients at baseline by performing PET-CT imaging over clinical staging who were referred to National Institute of Nuclear Medicine & Allied Sciences (NINMAS) for baseline staging.Patients and Methods: This cross sectional observational type of study was carried out in NINMAS from July 2017 to June 2018. A total of 26 newly diagnosed lymphoma patients referred to NINMAS for PET-CT scan for baseline staging were included in this study.  Results: Out of the 26 patients (14male and 12 female; mean age: 43.42 ± 17.98 years), 14(53.8%) patients were diagnosed with Hodgkin Lymphoma and 12(46.2%) with Non Hodgkin Lymphoma. In this study, 14(53%) patients were upstaged in PET-CT scan based staging in comparison to clinical staging. Key lesion was assessed by SUVmax in PET-CT scan of different stages of lymphoma. Highest key lesion was found in stage IV. Out of 26 patients, 7(27%) showed extranodal involvement in bone (3 lesions), liver (3 lesions), lung (1 lesion) and spleen (1 lesion).Conclusion: This study was undertaken to assess the role of FDG PET-CT scan for staging of lymphoma patient at baseline. In this study, 53% of the patients were upstaged in PET-CT scan based staging in comparison to clinical staging. PET-CT plays animportant role for accurate staging in lymphoma patients at baseline which increases the accuracy of subsequent response assessment.Bangladesh J. Nuclear Med. 22(1): 15-22, Jan 2019